Investigation of the survival of L-monocytogenes 4B SLCC 4013 strain in pastrami - Arslan, A; Gönülalan, Z; Kök, F; Dinçoglu, AH; Servi, K; Kara, H; Dogan, I (Scientific Technical Research Council Turkey, 1999)
This study was conducted to determine the lifespan of the pathogen L. monocytogenes 4B SLCC 4013 strain at different temperatures in pastrami produced in laboratory conditions. For the production of the pastrami, beef taken from the leg section (m. gluteobiceps femoris, m. gluteus spurficialis, m. gluteus medius et profundus) was used, containing 2.51 x 106 colony forming units (cfu/g) of listeria. The meat was divided into two groups. One group was salted with normal salt and the other group with salt containing 150 ppm NaNO3. The pastrami was vacuum packed after production. Some of the pastrami from each group was stored at shop temperature (+20 degrees C) and the rest was kept in a refrigerator (+4 degrees C). During production and 0, 30, 60 and 120 days after production, the samples were examined for viable aerobes, LLP, listeria, salt, nitrite, nitrate, pH and moisture. On day 120, 6.5 x 10(5) cfu/g viable aerobes, 6.2 x 10(5) cfu/g LLP, 6.92% salt, 39.10% moisture, 77.37 ppm NO3 56.87 ppm NO2 and pH 5.32 were determined in the pastrami with nitrate stored at shop temperature. These values in the pastrami without nitrate were 9.8 x 10(5) cfu/g, 4.4 x 10(5) cfu/g, 7.32%, 40.53%, 39.73 ppm, 43.43 ppm and pH 5.27, respectively. Listeria was not detected in either group. On 120 day, 1.6 x 10(6) cfu/g viable aerobes, 4.9 x 10(5) cfu/g LLP, 2.6 x 10(5) cfu/g listeria, 6.63% salt, 38.57% moisture, 111.23 ppm NO3, 42.70 ppm NO2 and pH 5.49 were determined in the pastrami with nitrate stored in the refrigerator. These values in pastrami without nitrate were 4.4 x 10(6) cfu/g, 4.7 x 10(5) cfu/g, 4.7 x 10(5) cfu/g, 6.87%, 40.47%, 60 ppm and pH 5.61 respectively. Using a linear regression model for listeria, it was observed that inhibition in pastrami with nitrate occurred at shop temperature on day 61 after production and on day 65 in pastrami without nitrate. It was observed that listeria activity continued in pastrami which was stored in the refrigerator.
Keywords: pastrami; L. monocytogenes; temperature; nitrate